Peritoneal dialysis-related peritonitis caused by Fusarium: a case report and literature review - Peng, Qin; Wu, Wenfeng; Deng, Lirong; Tong, Huanyue; Wu, Huiyi (Frontiers in Fungal Biology, 2025)
Fungal peritonitis represents a significant complication of peritoneal dialysis (PD) and can result in severe consequences. However, fungal peritonitis caused by Fusarium is relatively rare, and there is no standard treatment plan for reference. Consequently, clinical pharmacists participated in a drug therapy for a rare case of fungal peritonitis in PD caused by Fusarium through literature review and therapeutic drug monitoring. Finally, this case received oral voriconazole, and the plasma concentration was maintained above 2 μg/ml. Moreover, the patient achieved favorable outcomes.